DEVELOPMENT OF LINGUISTIC COMPETENCE OF FUTURE ENGLISH TEACHERS IN THE EDUCATIONAL PROCESS BASED ON SMART TECHNOLOGIES IN THE ERA OF DIGITAL TECHNOLOGIES AND INNOVATIONS - Fayzullayeva Dilnoza Ubaydulloyevna (Journals Park Publishing, 2023)
This article describes in detail the development of language competences among students of higher educational institutions of pedagogy, the characteristics of the current stage of education in the Republic, the development of linguistic competences of future English language teachers in the educational process based on smart technologies in the era of digital technologies and innovations.
Keywords: digital technologies, innovation, English language, social context, linguistic competences.